ELIMINATION OF DEFECTS OF THE BONE WALLS OF THE PARARONAL SINUSES WITH INJURIES OF THE MIDDLE ZONE OF THE FACE - Лиханова, Мария Анатольевна; Сиволапов, Константин Анатольевич; Павлов, Вениамин Витальевич; Климова, Ирина Ивановна (Medicine in Kuzbass, 2022)
The paper presents a comparative assessment of ways to eliminate defects in the bone walls of the paranasal sinuses. The study is based on our own experience in the use of implants made of porous titanium nickelide, titanium plates and titanium mesh. Elimination of defects of the paranasal sinuses was carried out in 71 victims. In all the operated patients, long-term treatment results were followed for 3 ± 1.2 years. The results were evaluated on the basis of clinical, radiological, functional and aesthetic data. The best results of treatment were obtained when using a titanium microgrid as a plastic material with its attachment with micro screws or titanium pins.